The Sexual Pleasure View of Sexual Desire. (2nd January 2020) - Halwani, Raja
Abstract: This paper defends the 'sexual pleasure view' of sexual desire—that sexual desire is for sexual pleasure. It does so by explaining the various aspects of the view, especially that of 'sexual pleasure' on which it relies, by explaining its important implications, by responding to various objections against it (that it relies on an impoverished notion of pleasure, e.g.), and by arguing against some of its main contenders (that sexual desire is for sexual activity, e.g.).